Rab GTPases as “eat me” signals for selective autophagy - Zhao, Yan G. (The Journal of cell biology, 2025)
Selective autophagy targets specific cellular cargo for degradation. In this issue, Zhao et al. (https://doi.org/10.1083/jcb.202410150) uncovered that Rab GTPases serve as pivotal “autophagy cues” for recruitment of cargo receptors to facilitate mitophagy, lipophagy, and xenophagy, contributing to the precise spatiotemporal regulation of selective autophagy.